Communication Strategies Among Tertiary Students in Mlearning - Sulaiman, Shahirah; Hussin, Supyan; Amir, Zaini (International Journal of Engineering and Technology, 2018)
The relentless wave of using mobile device in Malaysia, as a tool for teaching and learning in educational setting is incontestable. Multitudinous tertiary institutions have adapted this technology in their academic system; due to its approach which aids synchronous and asynchronous learning towards achieving educational outcomes. In spite of the rapid expansion medium employed in mobile learning [mLearning], students’ communicative competence in academic context is a major concern, especially when they are communicating in their native languages or being a bilingual user of the English language. Hence, this paper addresses the communication strategies in mLearning among tertiary students based on a quantitative research design conducted at Universiti Sains Islam Malaysia. The data were gathered from 125 students using a questionnaire which measured the learners’ frequency of the communication strategies used. Findings showed that the communication in mobile indicated that students employed varying degrees of communication strategies in mLearning. The results reflected an overview of students’ interaction in mLearning setting as it could be used to benefit academicians in assisting students with their communicative competence not only in- yet also out- of the mLearning context. Thus, several implications were further discussed in this study.